PERAN PENGASUH DALAM MENINGKATKAN MOTIVASI BELAJAR DI PANTI ASUHAN MUHAMMADIYAH KUBANG TUNGKEK KAB. LIMA PULUH KOTA - Rosi Dian Syafitri; Elviana, Elviana; Jhon Erita (CV. ADIBA AISHA AMIRA, 2024)
Motivation to learn is considered a very important factor for children, especially those living in orphanages. With the motivation given to them by their caregivers, they learn diligently to become human beings who are beneficial to the nation, state and religion. Of course, foster children in orphanages lack facilities and attention to their learning. Increasing the learning motivation of foster children using the group guidance method is an activity that involves all foster children to provide a special motivational boost for foster children when they want to achieve their learning goals. The aim of the research is to determine and increase children`s learning motivation at the muhammadiyah cab. Guguak district fifty cities through group tutoring services. The research use a descriptive qualitative method, this data collection technique is through a process of observation, interview and documentation. The results of this research reveal that there is an increase in the learning motivation of foster children an the muhammadiyah cab. Guguak district fifty cities.